FLASHlab@PITZ: New R&D platform with unique capabilities for electron FLASH and VHEE radiation therapy and radiation biology under preparation at PITZ. (December 2022) - Stephan, Frank; Gross, Matthias; Grebinyk, Anna; Aboulbanine, Zakaria; Amirkhanyan, Zohrab; Budach, Volker; Ehrhardt, Vincent Henrique; Faus-Golfe, Angeles; Frohme, Marcus; Germond, Jean-Francois; Good, James David; Grüner, Florian; et al.
Graphical abstract: Highlights: FLASH radiation therapy can reduce side effects in cancer therapy. PITZ accelerator offers unique parameter range for electron FLASH studies. Research plan to study electron FLASH radiation therapy at PITZ is presented. International collaboration of research institutes was formed. Preparations for realizing research platform are ongoing. Abstract: At the P hoto I njector T est facility at DESY in Z euthen (PITZ), an R&D platform for electron FLASH and very high energy electron radiation therapy and radiation biology is being prepared ( FLASH l a b @PITZ ). The beam parameters available at PITZ are worldwide unique. They are based on experiences from 20 + years of developing high brightness beam sources and an ultra-intensive THz light source demonstrator for ps scale electron bunches with up to 5 nC bunch charge at MHz repetition rate in bunch trains of up to 1 ms length, currently 22 MeV (upgrade to 250 MeV planned). Individual bunches can provide peak dose rates up to 10 14 Gy/s, and 10 Gy can be delivered within picoseconds. Upon demand, each bunch of the bunch train can be guided to a different transverse location, so that either a "painting" with micro beams (comparable to pencil beam scanning in proton therapy) or a cumulative increase of absorbed dose, using a wide beam distribution, can be realized at the tumor. Full tumor treatment can hence be completed within 1 ms, mitigating organ movement issues. With extremely flexible beam manipulation capabilities, FLASH l a b @PITZ will cover the current parameter range of successfully demonstrated FLASH effects and extend the parameter range towards yet unexploited short treatment times and high dose rates. A summary of the plans for FLASH l a b @PITZ and the status of its realization will be presented.